1999
DOI: 10.1300/j001v18n01_13
|View full text |Cite
|
Sign up to set email alerts
|

The Field Liaison Role in Schools of Social Work

Abstract: This paper presents the results of a survey of 69 schools of social work that asked who in each school is performing the role of the field liaison. In addition, the differences in the liaison roles of two large, midwestern schools of social work, one public, one private, are examined. How each approach impacts the partnership between school and agency is explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…After investigating the management structure of field programs, they found that all but one reported having a position titled Director of Field Instruction even though the programs varied considerably in other aspects, such as other field staff available and faculty involvement as liaisons. Burke, Condon, and Wickell (1999) found in their sample of 66 social work programs that 38% reported faculty members were field liaisons, and that all field liaisons (both faculty and other) made a mean average of 2.9 field visits per year. Ligon and Ward (2005) surveyed MSW field liaisons who reported a mean average of 2.2 field visits per semester.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After investigating the management structure of field programs, they found that all but one reported having a position titled Director of Field Instruction even though the programs varied considerably in other aspects, such as other field staff available and faculty involvement as liaisons. Burke, Condon, and Wickell (1999) found in their sample of 66 social work programs that 38% reported faculty members were field liaisons, and that all field liaisons (both faculty and other) made a mean average of 2.9 field visits per year. Ligon and Ward (2005) surveyed MSW field liaisons who reported a mean average of 2.2 field visits per semester.…”
Section: Literature Reviewmentioning
confidence: 99%